7th Edition NRP Brings Big Changes for NRP Instructors: The American Academy of Pediatrics. (June 2015) - Unknown
Abstract : The American Academy of Pediatrics; reprinted with permission from the Spring/Summer 2015 edition of the Instructor Update Newsletter, Volume 24, Number 1